(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this detailed article, the author delves into the diverse traditions and cultural events that define Uzbekistan’s unique identity. The narrative begins by highlighting the importance of hospitality and family in Uzbek customs, offering insights into traditional rituals like weddings and the Nowruz celebration. The article seamlessly transitions to an exploration of Uzbekistan’s vibrant festivals, such as the Sharq Taronalari International Music Festival and the Silk and Spices Festival, showcasing the country’s artistic heritage and Silk Road legacy. Moreover, the author emphasizes the significance of preserving Uzbekistan’s cultural heritage through initiatives aimed at safeguarding traditional crafts and restoring historic sites. The article provides a comprehensive overview of Uzbekistan’s cultural landscape, appealing to readers interested in Central Asian traditions, history, and festivals. Overall, this annotation encapsulates the article’s focus on Uzbekistan’s rich tapestry of customs and cultural events, offering a compelling glimpse into the country’s captivating heritage.